Психологічні особливості професійної мотивації персоналу сектору безпеки України : дисертація - Перепелиця, І. О.; Perepelytsia, I. O. (Харківський національний університет внутрішніх справ, 2025)
Дисертацію присвячено теоретико-емпіричному дослідженню особливостей професійної мотивації персоналу сектору безпеки і оборони України.

The dissertation is devoted to the theoretical and empirical study of the psychological characteristics of professional motivation among the personnel of the security and defense sector of Ukraine.
Psychological Characteristics of Professional Motivation of the Personnel of the Security Sector of Ukraine
Keywords: Україна; Дисертації. Dissertations; Dissertations; 053 Психологія; військовослужбовці; servicemen; персонал сил безпеки і оборони; професійна мотивація; мотивація державного служіння; типологія професійної мотивації; психологічні ресурси; ціннісно-смислова сфера; personnel of the security and defense sector; Ukraine; professional motivation; public service motivation; typology of professional motivation; psychological resources; value-semantic sphere